Effective communication skills for information professionals / Mohd Nizam Yunus ... [et al.] - Yunus, Mohd Nizam; Hashim, Husain; Azman, Kamarul Azwan; Md. Jali, Jafalizan (Faculty of Information Management, 2015)
An effective and good communication abilities are central to accomplishment in numerous parts of life. Numerous occupations require solid communication abilities and socially individuals with enhanced communication abilities more often than not appreciate better interpersonal associations with other parties. Effective communication provides useful benefits to a person especially if he or she is working in an organization that requires a good relation with clients and customers. In the field of records management, we do not only manage records but with the current situation, this area requires us to deal with external parties such as government departments and private sector and also from the members of the public. For example, some information institutions centers require external customers or clients for income generation. Clients and customers should be treated well and this requires an effective form of communication from information professionals. Imagine if the clients had to deal with staffs who do not know how to communicate effectively, the client may run away to other information institutions and they will lose their financial resources. This makes the information professionals should have the skills to communicate well in order to maintain the reputation of their records. An information professional also deals with government officials and also members of the public during their daily task. All of this requires good personal communication skills. Information institutions often received visitors such as libraries, archives, record centers and museums and one such way to handle visitors effectively is by using a good communication skills.